Sovereignties and Stolen Land - Jayson Cooper (2025)
This podcast explores Indigenous sovereignties and their erasure through colonial myths embedded in education and society. It examines Indigenous educational sovereignty, the impact of settler-colonial governance, and the ongoing resistance against dispossession. Drawing from the Uluru Statement from the Heart, Indigenous ways of knowing, and critical Indigenous scholarship, the discussion challenges Western notions of sovereignty, ownership, and education. The lecture interrogates the role of educators in truth-telling, deconstructing colonial narratives, and committing to Indigenous knowledge systems that centre relationality, sustainability, and accountability to Country.